1976
DOI: 10.1002/jsfa.2740271005
|View full text |Cite
|
Sign up to set email alerts
|

Freeze–thaw gelation of hen's egg yolk low density lipoprotein

Abstract: The freeze-thaw gelation of hen's egg yolk low density lipoprotein (1.d.l.) has been examined by viscometry, agarose gel filtration, electron spin resonance spectroscopy, electron microscopy and differential scanning calorimetry. The data indicate that the core lipids, the hydrocarbon chains of interfacial lipids of 1.d.l. and the sulphydryl, imino, amino and tyrosine groups in the side chains of 1.d.l. peptides are not directly involved in the gelation mechanisms. The gelation is caused by non-specific aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Most researchers were in agreement that dehydration of molecules is the first step in freeze-thaw gelation (Chang, Powrie, & Fennema, 1977;Kamat, Graham, Barratt, & Stubbs, 1976;Lovelock, 1957;Martin, Augustyniak, & Cook, 1964;Palmer, Ijichi, & Roff, 1970;Sato & Aoki, 1975;Telis & Kieckbusch, 1997;Wakamatu & Sato, 1980). Jaax and Travnicek (1968) and showed that slow cooling rates must be employed to induce gelation, as fast freezing of yolk in liquid nitrogen or oxygen resulted in little to no change of fluidity even with extended storage in low temperatures (33-49 d in -20°C).…”
Section: Freeze-thaw Induced Gelation Of Egg Yolkmentioning
confidence: 89%
See 3 more Smart Citations
“…Most researchers were in agreement that dehydration of molecules is the first step in freeze-thaw gelation (Chang, Powrie, & Fennema, 1977;Kamat, Graham, Barratt, & Stubbs, 1976;Lovelock, 1957;Martin, Augustyniak, & Cook, 1964;Palmer, Ijichi, & Roff, 1970;Sato & Aoki, 1975;Telis & Kieckbusch, 1997;Wakamatu & Sato, 1980). Jaax and Travnicek (1968) and showed that slow cooling rates must be employed to induce gelation, as fast freezing of yolk in liquid nitrogen or oxygen resulted in little to no change of fluidity even with extended storage in low temperatures (33-49 d in -20°C).…”
Section: Freeze-thaw Induced Gelation Of Egg Yolkmentioning
confidence: 89%
“…The first observation of freeze-thaw yolk gelation, as well as its inhibition by sucrose, was made by . Subsequent studies have confirmed reduced gelation via addition of other sugars such as fructose, sodium chloride and other salts, and proteolytic enzymes such as papain (Jaax & Travnicek, 1968;Kamat, Graham, Barratt, & Stubbs, 1976;Nowak, Powrie, & Fennema, 1966;Wakamatu & Sato, 1980;Wakamatu, Sato, & Saito, 1983).…”
Section: Freeze-thaw Induced Gelation Of Egg Yolkmentioning
confidence: 98%
See 2 more Smart Citations
“…With heat (Woodward & Cotterill, 1987a, b;Woodward, 1988) or freeze-thawing (Kamat et al, 1976;Chang et al, l 977) treatments, egg yolk may become viscous and thick, a condition known as gelation. The state of the yolk is also affected by salt even at room temperature (Mahadevan et al, 1969;Harrison & Cunningham, 1986).…”
mentioning
confidence: 99%